2021
DOI: 10.1126/sciadv.abg9450
|View full text |Cite
|
Sign up to set email alerts
|

Flexible artificial Si-In-Zn-O/ion gel synapse and its application to sensory-neuromorphic system for sign language translation

Abstract: Flexible artificial synapses are fabricated with a SIZO/ion gel hybrid structure forming a polyimide substrate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(27 citation statements)
references
References 73 publications
0
26
0
Order By: Relevance
“…The NL extraction method and LTP/LTD curves investigated under various pulse conditions are shown in Figures S13 and S14 (Supporting Information). [ 35 , 36 , 37 ] Finally, we demonstrate its applicability to hardware neural networks (HW‐NNs) using the “DNN+ NeuroSim” simulator. [ 38 ] The artificial neural network of the simulator was a CNN, and the Canadian Institute for Advanced Research‐10 (CIFAR‐10) image dataset was used for training (50 000 images) and inference (10 000 images) tasks.…”
Section: Resultsmentioning
confidence: 99%
“…The NL extraction method and LTP/LTD curves investigated under various pulse conditions are shown in Figures S13 and S14 (Supporting Information). [ 35 , 36 , 37 ] Finally, we demonstrate its applicability to hardware neural networks (HW‐NNs) using the “DNN+ NeuroSim” simulator. [ 38 ] The artificial neural network of the simulator was a CNN, and the Canadian Institute for Advanced Research‐10 (CIFAR‐10) image dataset was used for training (50 000 images) and inference (10 000 images) tasks.…”
Section: Resultsmentioning
confidence: 99%
“…4 b) [ 19 ]. Park et al [ 20 ] reported an ion-gel transistor-type ES using an ion-gel electrolyte composed of EMIM-TFSI and a gel matrix (Fig. 4 c).…”
Section: Neuromorphic Vision Sensor For Near-sensor Vision Computingmentioning
confidence: 99%
“…4 c). The mechanical flexibility of the gel allowed for the reliable fabrication and operation of ion-gel-based ESs on plastic substrates [ 20 23 ]. With this flexible in-memory computing device, tactile information from the human hand could be preprocessed directly, without the aid of an external computer device.…”
Section: Neuromorphic Vision Sensor For Near-sensor Vision Computingmentioning
confidence: 99%
“…The hardware neural networks made of silicon (Si) suffer from several drawbacks such as poor biocompatibility and rigidity and also require numerous circuit elements, making biointegration difficult. EDLTs are biocompatible, solution-processable, biodegradable, conformable, and soft, making them ideal for bioelectronic applications. , EDLTs modulated by a field-driven ion migration in the electrolyte layer could be operated with high transconductance, excellent stability of threshold voltage, linear weight updates, and strong ion-concentration-dependent switching properties, becoming a competitive alternative in this area. However, to date, there is no report on a flexible EDLT that provides all the aforementioned performance characteristics.…”
Section: Introductionmentioning
confidence: 99%